A dualidade do trabalho no modo de produção capitalista : impactos da reestruturação produtiva na subjetividade e na organização da classe trabalhadora - Cordeiro, Luisa Fernandes (2022)
This doctoral thesis aims to investigate how the duality that work assumes in the capitalist mode of production, understanding its two meanings, the ontological and its abstract meaning, impact on subjectivity and the organization of the working class. This is a quantitative and qualitative research based on the critical dialectic method based on historical materialism, however, the present study has a qualitative emphasis, therefore, it was composed through a non-probabilistic intentional sample of two (02) unions: The Sindicato dos Metalúrgicos da Grande Porto Alegre (STIMEPA) and the Sindicato dos Empregados em Estabelecimento Bancários do Rio Grande do Norte (SEEB/RN). The research technique used for the realization of this Thesis was triangulation, contemplating online collections with union leaders, documentary analyses and bibliographic review. Thus, the sources that were used for the triangulation were: the analysis of the social context in contemporaneity, from a conceptual thickening based on authors whose productions could contribute to the thickening of the theme of this research, the perception of the workers, represented here through the union leaders, and the analysis of documents that would deepen the data about the union organization of formal workers. It is understood that work is central to this thesis, and in this sense, throughout the second chapter, the understanding of social being was discussed, therefore, its ontology, the law of value, the forms that work assumes in the order of capital, demarcating the time of analysis from the 1970s. It is understood that the toyist management technique is a transforming landmark in the way of organizing and producing. In this journey, fundamental categories such as ideology, alienation, and the capture of subjectivity were discussed. Then, in the third chapter, a historical review was carried out on the formation of the working class worldwide, then the Brazilian reality was approached, presenting its particularities and, finally, unionism and the union movement - this being one of the several locus of action and organization of the working class -, from its initial roles until its forms of organization in the present time. The third chapter ends by presenting the concepts and importance of grassroots work, which is a space to be fostered for the creation of new perspectives. Finally, the contradictory character of work in capitalism and some limits and possibilities imposed on the class struggle to face reality and to build subjects of a new type, ethical and aesthetic, were presented as part of the process of overcoming sociability. capitalist.